Answer:
$311.20
Step-by-step explanation:
Here we are required to use the Compound interest formula for finding the Amount at the end of 9th year
The formula is given as
[tex]A=P(1+\frac{r}{n})^{tn}[/tex]
Where ,
A is the final amount
P is the initial amount = $200
r is the rate of interest = 5% annual = 0.05
n is the frequency of compounding in a year ( Here it is compounding monthly) = 12
t is the time period = 9
Now we substitute all these values in the formula and solve for A
[tex]A=200(1+\frac{0.05}{12})^{9\times 12}[/tex]
[tex]A=200(1+0.00416)^{108}[/tex]
[tex]A=200(1.00416)^{108}[/tex]
[tex]A=200 \times 1.556[/tex]
[tex]A=311.20[/tex]
Hence the amount after 9 years will be $311.20
A group of students is arranging squares into layers to create a project. The first layer has 5 squares. The second layer has 10 squares. Which formula represents an arithmetic explicit formula to determine the number of squares in each layer?
Answer:
[tex]a_n=5n[/tex]
Step-by-step explanation:
They gave us the first two terms in the sequence which is 5,10.
They then tell us the sequence is arithmetic which means all you need to do to get the next term is add/subtract.
To get from 5 to 10, you would need to add 5.
So that is what we are doing every time here.
5,10,15,20,25,... so on...
Now we want to make an equation for this.
When you see arithmetic sequence, you should think linear equations.
x | y
-----------
1 5
2 10
3 15
4 20
Can you see the relationship between y and x?
Slope is 5 because that is what the sequence is going up by.
y=5x+b
Maybe you can already see b is 0. If not, you can use a point on the line to find b.
Let's use (1,5).
5=5(1)+b
5=5+b
0=b
So b=0.
The equation is y=5x.
Our since we are talking about sequences maybe you prefer to say [tex]a_n=5n[/tex]
How old am I if 500 reduced by 3 times my age is 278?
Let your age = X
Now you have 500 - 3x = 278
Subtract 500 from each side:
-3x = -222
Divide both sides by -3:
x = -222 / -3
x = 74
You are 74 years old.
The age of an old man is 74 years old.
What is a word problem?A word problem is a verbal description of a problem situation. It consists of few sentences describing a 'real-life' scenario where a problem needs to be solved by way of a mathematical calculation.
For the given situation,
Let the age of an old man be x.
500 reduced by 3 times my age is 278 can be expressed as
⇒ [tex]500-3x=278[/tex]
⇒ [tex]500-278=3x[/tex]
⇒ [tex]222=3x[/tex]
⇒ [tex]x=\frac{222}{3}[/tex]
⇒ [tex]x=74[/tex]
Hence we can conclude that the age of an old man is 74 years old.
Learn more about word problems here
brainly.com/question/20594903
#SPJ2
How does the graph of f(x) = 5
cos 1/2 X
Answer:
The graph of [tex]f(x)=5\cos(\frac{1}{2}x)[/tex] is a vertical stretch of 5 units and a horizontal stretch by 2 units of the parent graph
Step-by-step explanation:
We want to find out how the graph of [tex]f(x)=5\cos(\frac{1}{2}x)[/tex] compare with the graph of the parent function [tex]g(x)=\cos (x)[/tex].
We can observe that the transformation applied to the basic cosine function is of the form:
[tex]y=A \cos Bx[/tex]
The [tex]A=5[/tex] is a vertical stretch by a factor of 5 units.
[tex]B=\frac{1}{2}[/tex] is a horizontal stretch by a factor of 2 units.
Therefore the graph of [tex]f(x)=5\cos(\frac{1}{2}x)[/tex] will stretch vertically by a factor of 5 units and stretch horizontally by a factor of 2 units as compared to [tex]g(x)=\cos (x)[/tex].
See attachment
Solve for x 3 - square root of x = 0
Answer:
x = 9Step-by-step explanation:
[tex]3-\sqrt{x}=0\\\\\text{Domain:}\ x\geq0\\\\3-\sqrt{x}=0\qquad\text{add}\ \sqrt{x}\ \text{to both sides}\\\\3=\sqrt{x}\to\sqrt{x}=3\\\\\text{Use the de}\text{finition of a square root:}\ \sqrt{a}=b\iff b^2=a\\\\\sqrt{x}=3\iff x=3^2\\\\x=9[/tex]
Someone please help me with this question. I would greatly appreciate it. Please and thank you.
[tex]\dfrac{15(15-1)}{2}=\dfrac{15\cdot14}{2}=15\cdot7=105[/tex]
What is the following product? square root 10× square root 10
[tex]\huge{\boxed{10}}[/tex]
We can rewrite this using an exponent. [tex]\sqrt{10}^2[/tex]
When you square a square root, you basically just cancel out the square root, leaving whatever was inside the square root symbol. In this case, you end up with a final answer of [tex]\boxed{10}[/tex].
Step-by-step explanation:
First, you must find the square root of 10, which is 3.16.
Now, multiply 3.16x3.16, or find 3.16 squared.
This is 9.98
There are 12 girls and 10 boys in the student council. What is the ratio of the number of girls to the total number of members? F. 6:5. G. 5 to 6. H. 6 to 11. I. 1 to 2.
Answer:
i think the answer is choice H
Step-by-step explanation:
the number of girls to total number of members is 12:22, if you simplify this it's 6:11
Answer:
6:11
Step-by-step explanation:
There are 12 girls.
There are 12+10 member in all.
That means there are 22 members in all.
So the ratio of girls to total members is 12 to 22 or 12:22. To reduce this, look for a common factor. 12 and 22 both share 2 as a common factor so divide both by 2 gives you 6:11.
Nasheem is going to make breakfast for his family. He has a carton of dozen eggs and uses 2/3 of them. How many eggs did Nasheem use? How many eggs does he have left?
Answer:
Step-by-step explanation:
He uses (2/3)(12 eggs) = 8 eggs.
He has (12-8), or 4, eggs left.
Answer:
Step-by-step explanation:
Number of eggs = 1 dozen = 12 eggs
Number of used eggs = 2/3 * 12 (Total eggs will be multiplied by used eggs)
2/3*12
2*4
=8 eggs
Number of used eggs= 8 eggs
To find the number of left eggs. Simply subtract the used eggs from total eggs
12-8 = 4eggs
4 eggs were left....
if f(x)=4x2=1 and g(x)=x2-5, find (f-g)(x)
A:3x2+6
B:5x2-6
C:3x2-4
D:5x2-4
For this case we have the following functions:
[tex]f (x) = 4x ^ 2 + 1\\g (x) = x ^ 2-5[/tex]
We must find[tex](f-g) (x):[/tex]
By definition of operations with functions we have:
[tex](f-g) (x) = f (x) -g (x)[/tex]
So:
[tex](f-g) (x) = f (x) -g (x) = 4x ^ 2 + 1- (x ^ 2-5) = 4x ^ 2 + 1-x ^ 2 + 5 = 3x ^ 2 + 6[/tex]
Answer:
Option A
[tex]3x ^ 2 + 6[/tex]
Ken wants to purchase a boat. The purchase price of the boat is $ 15 , 000. The dealership will allow him to pay cash or finance the boat for a down payment of $ 3 , 000.00 and 48 monthly payments of $ 300.00. Ken chose to finance the boat.
In finance, the buyer pays more when choosing to finance the boat rather than paying cash upfront due to additional fees included in the payments.
Explanation:The subject area of the question is Mathematics, specifically Financial Mathematics. The question is asking about the total cost Ken will pay for the boat if he chooses to finance it. The down payment is $3000 and he will make 48 monthly payments of $300, totaling $14,400. Therefore, Ken will pay a total of $17,400 when financing the boat, which is $2,400 more than the cash purchase price.
Learn more about Financial Mathematics here:https://brainly.com/question/28975181
#SPJ12
To find the total amount paid for the boat, add the down payment to the product of the monthly payments and the number of payments.
Explanation:To find the total amount paid for the boat, we need to calculate the total future amount. The down payment is $3,000 and there are 48 monthly payments of $300 each.
The total future amount can be calculated using the formula:
Total Future Amount = Down Payment + Monthly Payments * Number of Payments
Plugging in the values, we get:
Total Future Amount = $3,000 + $300 * 48 = $17,400
Therefore, Ken will pay a total of $17,400 for the boat.
Learn more about Calculating the total amount paid for the boat here:https://brainly.com/question/34045673
#SPJ12
Multiply
6.421. 10 =
0.6421
• 64.21
64210
6,421
Gujb
Answer:
64.21
Step-by-step explanation:
Here we are given with the a number in decimals and need to find its product with 10.
please note the rule of multiplication in decimals . When we multiply any decimal with 10, 100, 1000 , 10000 and so on.. the position of decimal in the number given to us shifts to its right by the number of places as we have the number of 0 in the multiplier
6.421 X 10
here we have only one 0 in the multiplier , hence the position of decimal in 6.421 will be shifted to one place towards right
6.421 x 10 = 64.21
Answer:
64.21
Step-by-step explanation:
If 0 is in quadrant 3 and sin0= -3/5 then cos0=
If angle θ is in quadrant 3 and the value of sin θ = -3/5, then we can say that; cos θ = -4/5
How to work with Trigonometric Ratios?
We are told that the angle θ is in quadrant 3.
Now, we are told that; sin θ = -3/5
In the third quadrant, only tan θ is positive.
Thus, cos θ will be negative.
Thus;
cos θ = -4/5
Read more about Trigonometric Ratios at; https://brainly.com/question/13276558
#SPJ1
Answer:
If angle θ is in 3rd quadrant and the value of [tex]sin\theta =\frac{-3}{5}[/tex], then [tex]cos\theta =\frac{-4}{5}[/tex]
Step-by-step explanation:
Given that , angle θ is in 3rd quadrant and the value of [tex]sin\theta =\frac{-3}{5}[/tex]
We know that ,
[tex]sin^2\theta + cos^2\theta =1[/tex]
[tex]cos^2\theta =1 - sin^2\theta[/tex]
By replacing the value of [tex]sin\theta =\frac{-3}{5}[/tex] we get,
[tex]cos^2\theta =1 - (\frac{-3}{5})^2[/tex]
[tex]cos^2\theta =1 - \frac{9}{25} = \frac{16}{25}[/tex]
Taking roots at the end of both sides we get,
[tex]cos\theta = \frac{4}{5}[/tex] or [tex]cos\theta = \frac{-4}{5}[/tex]
We know that , In third quadrant, only tan θ and cot θ are positive.
Thus, cos θ will be negative.
So [tex]cos\theta = \frac{-4}{5}[/tex]
Read more about Trigonometric Ratios at; brainly.com/question/13276558
#SPJ1
(4.0 •10^6) divided by (5.0•10^9) in scientific notation
Answer: [tex]8.0*10^{-4}[/tex]
Step-by-step explanation:
You need to remember the Quotient of powers property:
[tex]\frac{a^m}{a^n}=a^{(m-n)}[/tex]
Then, given the expression:
[tex]\frac{(4.0*10^6)}{(5.0*10^9)}[/tex]
You must divide the coefficients and subtract the exponents. Then:
[tex]=0.8*10^{-3}[/tex]
In order to write this result in Scientific notation form, you need to move the decimal point one place to the right. Therefore, you get:
[tex]=8.0*10^{-4}[/tex]
Use multiples to write 2 fractions equivalent to 7/9
Answer:
14/18 and 49/63
Step-by-step explanation:
14/18 and 49/63 are equivalent to 7/9.
7 x 2 = 14
9 x 2 = 18
Therefore, 14/18
7 x 7 = 49
9 x 7 = 63
Therefore, 49/63
Answer:
21/27 and 42/54
Step-by-step explanation:
therefore, 21/27 and 42/54 are equivalent to 7/9
7 x 3=21
9 x 3= 27
Therefore, 21/27
7 x 6= 42
9 x6 = 54
Therefore, 42/54
Find the standard equation and graph of a parabola that matches the given set of characteristics. vertex (0, 0) focus (-2, 0)
The standard equation of a parabola with vertex (0, 0) and focus (-2, 0) is y^2 = -8x. It opens to the left with the directrix x = 2.
To find the standard equation of a parabola with vertex (0, 0) and focus (-2, 0), we can use the definition of a parabola as the set of all points equidistant from a point (the focus) and a line (the directrix).
Since the focus is at (-2, 0), the directrix is a vertical line equidistant from the vertex on the opposite side of the focus, which is x = 2. The distance between the vertex and the focus (or the vertex and the directrix) is 2 units, so q = 2. This means that the parabola opens to the left.
The standard equation for a parabola that opens horizontally is of the form (y - k)^2 = 4p(x - h), where (h, k) is the vertex and p is the distance from the vertex to the focus. Here, p = -2 because the parabola opens to the left.
Therefore, the standard equation for the given parabola is y^2 = -4(2)x or y^2 = -8x.
help pls ;-;
What is the perimeter of the figure?
a. 180 in.
b. 64 in.
c. 65 in.
d. 72 in.
Answer:
180 in
Step-by-step explanation:
The perimeter is just the sum of the lengths of the sides of the shape.
So all we need to do here is:
40+10+(40-18)+(50-10)+18+50.
I got (40-18) for the bottom of the top rectangle, the part that is poking out.
I got (50-10) for the right side of the rectangle that is poking out towards the bottom.
40+10+(40-18)+(50-10)+18+50
40+10+22 +40 +18+50
50 +62 +68
50+62+68
112+68
180
180 in
I'm going to post a drawing here to show the lengths I was talking about:
rectangle ABCD is shown on the coordinate grid below. which of the following graphs represent the translation of rectangle ABCD over the following: (x, y) —> (x + 1, y-2)?
Answer:
the answer is c glad i could help
2. Given the objective function C=3x−2y and constraints x≥0, y≥0, 2x+y≤10, 3x+2y≤18, find the maximum value of C. (2.0 Points)
Answer:
The maximum value of C is 15
Step-by-step explanation:
we have
[tex]x\geq 0[/tex] -----> constraint A
[tex]y\geq 0[/tex] -----> constraint B
[tex]2x+y\leq 10[/tex] -----> constraint C
[tex]3x+2y\leq 18[/tex] -----> constraint D
using a graphing tool
The solution area of the constraints in the attached figure
we have the vertices
(0,0),(0,9),(2,6),(5,0)
Substitute the value of x and the value of y in the objective function
(0,0) -----> [tex]C=3(0)-2(0)=0[/tex]
(0,9) -----> [tex]C=3(0)-2(9)=-18[/tex]
(2,6) -----> [tex]C=3(2)-2(6)=-6[/tex]
(5,0) -----> [tex]C=3(5)-2(0)=15[/tex]
therefore
The maximum value of C is 15
To find the maximum value of the objective function $C = 3x - 2y$ subject to the given constraints, we can use the method of linear programming. We have the given constraints:
1. $x \geq 0$ (x is non-negative)
2. $y \geq 0$ (y is non-negative)
3. $2x + y \leq 10$
4. $3x + 2y \leq 18$
The first two constraints define that our solution must lie in the first quadrant of the Cartesian plane, as both x and y must be non-negative.
The third and fourth constraints define linear inequalities which we will represent graphically to find the feasible solution region.
Let's start by finding the intercepts of the lines represented by constraints 3 and 4:
For the third constraint, $2x + y = 10$:
- If $x = 0$, then $y = 10$.
- If $y = 0$, then $x = 5$.
For the fourth constraint, $3x + 2y = 18$:
- If $x = 0$, then $y = 9$.
- If $y = 0$, then $x = 6$.
Plotting these lines on a graph will give us two lines which intersect with the axes to form their intercepts and bound a certain area on the first quadrant.
The feasible region is the area that satisfies all the inequalities simultaneously, including the non-negativity constraints of x and y.
Next, we find the vertices of the feasible region. The vertices occur where the lines of the constraints intersect each other as well as with the axes. From the graph, we could find that the feasible region is a polygon formed by intersecting the lines corresponding to the constraints. The vertices are:
1. Where $2x + y = 10$ and $3x + 2y = 18$ intersect.
2. Where $2x + y = 10$ and the y-axis intersect.
3. Where $3x + 2y = 18$ and the x-axis intersect.
We solve for each vertex by solving the system of equations corresponding to the constraints that intersect:
For vertex 1, solving $2x + y = 10$ and $3x + 2y = 18$ simultaneously, we could do this by multiplying the first equation by 2 to eliminate y, and then subtract it from the second equation:
$4x + 2y = 20$
$3x + 2y = 18$
Subtracting the second equation from the first gives
$x = 2$
Plug this value of x into one of the original equations:
$2(2) + y = 10$
$4 + y = 10$
$y = 6$
So, vertex 1 is at (2, 6).
Vertex 2 is at the y-intercept of $2x + y = 10$ which is (0, 10).
Vertex 3 is at the x-intercept of $3x + 2y = 18$ which is (6, 0).
Now, we calculate the value of the objective function at each vertex:
For (2, 6):
$C = 3(2) - 2(6) = 6 - 12 = -6$
For (0, 10):
$C = 3(0) - 2(10) = 0 - 20 = -20$
For (6, 0):
$C = 3(6) - 2(0) = 18 - 0 = 18$
The maximum value of C within the feasible region is found at the intersection points of the constraints. Among the calculated values for the objective function $C$ at the vertices, the maximum value is $18$ at the point $(6, 0)$.
Therefore, the maximum value of the objective function $C = 3x - 2y$ given the constraints is 18.
For O D, find mCBE.
A. 311.1°
B. 311.20
C.352 29
D. 332.19
Check the picture below.
Answer:
i think its d
Step-by-step explanation:
The height y (in feet) of a ball thrown by a child is
y=−1/12x^2+6x+3
where x is the horizontal distance in feet from the point at which the ball is thrown.
(a) How high is the ball when it leaves the child's hand? (Hint: Find y when x=0)
Your answer is y=_______
(b) What is the maximum height of the ball? _______
(c) How far from the child does the ball strike the ground? ______
Answer:
Step-by-step explanation:
a)
y=−1/12x^2+6x+3
y=−1/12(0)^2+6(0)+3
y = 3
b)
y=−1/12x^2+6x+3
y = -1/12 (x^2-72x) + 3
y = =-1/12 (x^2-72x+1296-1296) +3
y = -1/12(x^2 -72x +1296) + 108 + 3
y = -1/12 (x - 36)^2 +111
maximum height of the ball is 111 feets
c)
y = -1/12 (x - 36)^2 +111
0 = -1/12 (x - 36)^2 +111
-111 = -1/12 (x - 36)^2
1332 = (x - 36)^2
36.497 = x - 36
x = 72.497
How far from the child does the ball strike the ground = 72.497 feets
The ball is 3 feet high when it leaves the child's hand. The maximum height of the ball is 6 feet. The ball strikes the ground 2 feet from the child.
Explanation:(a) To find the height of the ball when it leaves the child's hand, we need to substitute x=0 into the equation for y. Therefore, y=(-1/12)(0)^2+6(0)+3=3. So, the ball is 3 feet high when it leaves the child's hand.
(b) The maximum height of the ball can be found by determining the vertex of the parabolic equation. The equation is in the form of y=ax^2+bx+c, where the vertex is located at x=-b/2a. In this case, a=-1/12 and b=6. Therefore, x=-6/(2(-1/12))=-6/(-1/6)=-6(-6)=6 feet. So, the maximum height of the ball is 6 feet.
(c) To determine how far from the child the ball strikes the ground, we need to find when the ball's height is 0. Set y to 0 and solve for x. 0=(-1/12)x^2+6x+3. This equation can be solved using factoring or the quadratic formula. The solutions are x=-36 and x=2. Therefore, the ball strikes the ground 2 feet from the child.
Step 1: -10 + 8x < 6x-4
Step 2: -10 <-2x - 4
Step 3: -6 <-2x
Step 4:
What is the final step in solving the inequality --215-4x)
6x - 4?
O x<-3
O x>-3
O x<3
O x>3
Help!!
Answer:
The final step in solving inequality is x>3.
Step-by-step explanation:
To solve this problem, first thing to do is switch sides of -2x>-6, and divde -2 from both sides.
-2x>-6
-2x/-2>-6/-2
Divide numbers from left to right.
-6/-2=3
The final step in solving the inequality is x>3, which is our answer.
I hope this helps!
Thank you! for submitting question on Brainly.
Whatis the domain and range of f(x)=2[x-4]
Answer:
Domain: All Real Numbers
Range: All real numbers
Step-by-step explanation:
The given function is:
[tex]f(x) = 2(x-4)[/tex]
Domain:
The given function will not be undefined on any value of x as there is no denominator involved in the function.
So, the domain of the function is all real numbers
Range:
Similarly the range of the function is also all real numbers.
The length of each leg of an isosceles right triangle is 4 cm. What is the length of the hypotenuse
Answer:
5.65 cm
Step-by-step explanation:
We are given that the length of each leg of an isosceles right triangle is 4 cm and we are to find the length of the hypotenuse.
For this, we will use the Pythagoras Theorem:
[tex] a ^ 2 = b ^ 2 + c ^ 2 [/tex]
where [tex]a[/tex] is the hypotenuse.
[tex] a ^ 2 = 4 ^ 2 + 4 ^ 2 [/tex]
[tex] \sqrt { a ^ 2} = \sqrt { 3 2 } [/tex]
[tex] a = 5 . 6 5 [/tex]
Therefore, the length of the hypotenuse is 5.65 cm.
Answer:
hypotenuse = 4√2
Step-by-step explanation:
It is given that, the length of each leg of an isosceles right triangle is 4 cm
To find the hypotenuse
From the given information we get the given triangle is a right triangle with angles 45°, 45° and 90°
Therefore the side are in the ration 1 : 1 : √2
Here two legs are give
leg1 : leg2 : hypotenuse = 4 : 4 : 4√2
Therefore hypotenuse = 4√2
I dentify the domain and range and sketch the graph
[tex] y = sqrt { - x - 3 - 3} [/tex]
Answer:
Step-by-step explanation:
y=√(-x-3) - 3
y exisit : - x -3 ≥ 0
- x ≥ 3
x ≤ - 3 the domain is : D=] -∞,-3 ]
y=√(-x-3) - 3
y + 3 = √(-x-3)
x exisit : y + 3 ≥ 0 ; y ≥ -3
the range is : w = [- 3,+ ∞ [
look the graph
What is the solution to this equation?
x- 12 = 9
Answer:
x = 21
Step-by-step explanation:
x- 12 = 9
Add 12 to each side
x- 12+12 = 9+12
x = 21
Answer:
[tex]\huge \boxed{x=21}[/tex]
Step-by-step explanation:
[tex]\Huge\textnormal{Add 12 from both sides of the equation.}[/tex]
[tex]\displaystyle x-12+12=9+12[/tex]
[tex]\Huge \textnormal{Simplify and solve to find the answer.}[/tex]
[tex]\displaystyle 9+12=21[/tex]
[tex]\huge \boxed{x=21}[/tex], which is our answer.
Can somebody help thanks if you do
Answer:
It is A i believe.
Step-by-step explanation:
Because, 15/100 = 0.15 and y is your regular price so;
y - 0.15
Sorry had to rewrite what i did, but i hope my answer has helped you.
14 points!!
Is this shape a polygon?
Answer:
TRUEStep-by-step explanation:
A polygon is a plane figure that is described by a finite number of straight line segments connected to form a closed polygonal chain or polygonal circuit.
Because of a problem in the program, the timer in a video player did not begin counting until the video had been playing for several seconds. The player began counting at 0 seconds, even though the video had already played 190 frames. The video plays 25 frames per second. How many frames had the video already played when the time was equal to -3 2/5 seconds?
Answer:
105 frames
Step-by-step explanation:
Given that 25 frames are played per second
25 frames= 1 sec
The video already played 3 and 2/5 seconds before the player started to count 0
Write 3 and 2/5 seconds as an improper fraction
=(5*3)+2 / 5 = 17/5 seconds
Multiply by 25 frames
17/5 *25 =85 frames
So according to the video counter,after 17/5 seconds,it should count 85 frames.However,at 0 seconds,it indicated a count of 190 frames.Thus,to get the number of frames that were already in count you subtract 85 frames from the 190 frames.
190-85=105 frames.
The video had played 275 frames when the timer showed [tex]-3\frac{2}{5}[/tex] seconds.
To determine how many frames had been played when the timer showed [tex]-3\frac{2}{5}[/tex] seconds, we first need to convert [tex]-3\frac{2}{5}[/tex] seconds to an improper fraction or decimal. We have [tex]-3\frac{2}{5}[/tex] = [tex]-\frac{17}{5}[/tex] seconds.
Since the video plays at a rate of 25 frames per second, we can calculate the number of frames played during [tex]-\frac{17}{5}[/tex] seconds as follows:
Total frames = 25 frames/second × [tex]-\frac{17}{5}[/tex] seconds = -85 frames.
This means that 85 frames had been played before the timer started counting (since negative time indicates frames played before the recorded start time).
Since at 0 seconds, the video had already played 190 frames, we add the frames played during the negative time interval:
Total frames = 190 frames (initial) + 85 frames = 275 frames.
Type the expression as radicals.
Y3/5
Answer:
[tex]\sqrt[5]{y^{3} }[/tex]
Step-by-step explanation:
[tex]y^{\frac{3}{5} } = y^{\frac{1}{5} * 3}[/tex] = [tex]\sqrt[5]{y^{3} }[/tex]
This is true because of the fractional exponent rule.
Answer:
Step-by-step explanation:If
n
is a positive integer that is greater than
x
and
a
is a real number or a factor, then
a
x
n
=
n
√
a
x
.
a
x
n
=
n
√
a
x
Use the rule to convert
y
3
5
to a radical, where
a
=
,
x
=
, and
n
=
.
5
√
y
3
Find the average rate of change of f(x) = 2x2 – 7x from x = 2 to x=6.
Simplify your answer as much as possible.
Answer:
-6Step-by-step explanation:
[tex]\text{The average rate of change of function}\ f(x)\\\text{over the interval}\ a\leq x\leq b\ \text{is given by this expression:}\\\dfrac{f(b)-f(a)}{b-a}\\\\f(x)=2x^2-7x\\\\\text{Put the values of x = 2 and x = 6 to the equation of the function:}\\\\f(2)=2(2^2)-7(2)=2(4)-14=8-14=-6\\f(6)=2(6^2)-7(6)=2(36)-42=72-42=-30\\\\\dfrac{f(6)-f(2)}{6-2}=\dfrac{-30-(-6)}{4}=\dfrac{-24}{4}=-6[/tex]